2021
DOI: 10.4103/joacp.joacp_405_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of analgesic efficacy of buprenorphine transdermal patch and fentanyl patch in management of postoperative pain after arthroscopic lower limb surgery

Abstract: Background and Aims: Transdermal opioids are newer modality in use for the control of postoperative pain, because of its noninvasiveness, longer duration of action, sustained blood levels, and with minimal side effects. The study was aimed to evaluate the efficacy of analgesia of buprenorphine patch 10, 20 μg·h -1 and fentanyl patch 25 μg·h -1 for relief of pain in the postoperative period in patients undergoing arthroscopic lower limb surgerie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…21 Khandelwal et al, very recently in 2021, evaluated the efficacy of analgesia of buprenorphine patch 10, 20 µg•h -1 and fentanyl patch 25 µg•h -1 for relief of pain in the postoperative period in patients undergoing arthroscopic lower limb surgeries and concluded that in arthroscopic lower limb surgery, buprenorphine patch (20 µg•h -1 ) applied 12 h before surgery is an effective post-operative analgesic and it is not associated with any significant adverse effects. 22 Niyogi et al, in 2017, evaluated the analgesic efficacy of buprenorphine patch for post-operative pain relief in patients undergoing spinal instrumentation surgery. They found that time to first post-operative rescue analgesic (tramadol) requirement was much delayed and also reduced in patients having TDB.…”
Section: Discussionmentioning
confidence: 99%
“…21 Khandelwal et al, very recently in 2021, evaluated the efficacy of analgesia of buprenorphine patch 10, 20 µg•h -1 and fentanyl patch 25 µg•h -1 for relief of pain in the postoperative period in patients undergoing arthroscopic lower limb surgeries and concluded that in arthroscopic lower limb surgery, buprenorphine patch (20 µg•h -1 ) applied 12 h before surgery is an effective post-operative analgesic and it is not associated with any significant adverse effects. 22 Niyogi et al, in 2017, evaluated the analgesic efficacy of buprenorphine patch for post-operative pain relief in patients undergoing spinal instrumentation surgery. They found that time to first post-operative rescue analgesic (tramadol) requirement was much delayed and also reduced in patients having TDB.…”
Section: Discussionmentioning
confidence: 99%
“…Groups of the 175 patients were formed [17]. The postoperative pain was assessed using the numerical rating scale (NRS).…”
Section: Postoperative Considerationsmentioning
confidence: 99%
“…compared two doses of buprenorphine (10 μgh -1 and 20 μgh -1 ) with fentanyl (25 μgh -1 ) in adult patients undergoing lower limb arthroscopic surgery. [ 2 ] They found TDB patch (20 μgh -1 ) to be an effective postoperative analgesic without any significant undesirable effects.…”
mentioning
confidence: 99%
“…Alternative analgesics should be started till the effect of TDS drugs comes in 12–24 h, whereas in the index study, the usual analgesics were withheld the day before surgery when the patches were applied. [ 2 ]…”
mentioning
confidence: 99%
See 1 more Smart Citation